2003
DOI: 10.1074/jbc.m213252200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MCM4 as a Target of the DNA Replication Block Checkpoint System

Abstract: Inhibition of the progression of DNA replication prevents further initiation of DNA replication and allows cells to maintain arrested replication forks, but the proteins that are targets of the replication checkpoint system remain to be identified. We report here that human MCM4, a subunit of the putative DNA replicative helicase, is extensively phosphorylated in HeLa cells when they are incubated in the presence of inhibitors of DNA synthesis or are exposed to UV irradiation. The data presented here indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 43 publications
3
84
1
Order By: Relevance
“…9). In human cells, MCM4 also undergoes caffeine-sensitive, checkpointdependent phosphorylation, but a direct role for ATR was not addressed (37). While this manuscript was in preparation, it was reported that ATM and ATR phosphorylate mammalian MCM2 on a site analogous to the one that we have found in Xmcm2 (38 (lanes 1 and 2), geminin ( lanes 3 and 4), or caffeine (lanes 5 and 6).…”
Section: Discussionmentioning
confidence: 91%
“…9). In human cells, MCM4 also undergoes caffeine-sensitive, checkpointdependent phosphorylation, but a direct role for ATR was not addressed (37). While this manuscript was in preparation, it was reported that ATM and ATR phosphorylate mammalian MCM2 on a site analogous to the one that we have found in Xmcm2 (38 (lanes 1 and 2), geminin ( lanes 3 and 4), or caffeine (lanes 5 and 6).…”
Section: Discussionmentioning
confidence: 91%
“…MCMs proteins have been shown to be direct targets of ATM/ATR kinases (Cortez et al, 2004;Ishimi et al, 2003;Shi et al, 2007;Yoo et al, 2004), suggesting that the MCMs may be targets or effectors of the replication checkpoint. It has been shown that the phosphorylation of MCM4 in the checkpoint control inhibits DNA replication, which includes blockage of DNA fork progression through inactivation of the MCM complex (Ishimi et al, 2003).…”
Section: Is Udu Required For Dna Replication?mentioning
confidence: 99%
“…It has been shown that the phosphorylation of MCM4 in the checkpoint control inhibits DNA replication, which includes blockage of DNA fork progression through inactivation of the MCM complex (Ishimi et al, 2003). Thus, the DNA sequence fidelity, together with associated chromatin structure must be accurately replicated to maintain genetic and epigenetic information through cell generations.…”
Section: Is Udu Required For Dna Replication?mentioning
confidence: 99%
See 1 more Smart Citation
“…The retinoblastoma protein, cyclin D, and papillomavirus E6 protein also bind to MCM7 (22)(23)(24). The MCM complex is also an indirect target of checkpoint signaling via modulation of cyclin-dependent kinase-mediated MCM4 phosphorylation (25).…”
mentioning
confidence: 99%